2016
DOI: 10.1136/annrheumdis-2015-209059
|View full text |Cite
|
Sign up to set email alerts
|

A single endoplasmic reticulum aminopeptidase-1 protein allotype is a strong risk factor for Behçet's disease in HLA-B*51 carriers

Abstract: Introduction Endoplasmic reticulum aminopeptidase 1 (ERAP1) protein is highly polymorphic with numerous missense amino acid variants. We sought to determine the naturally occurring ERAP1 protein allotypes and their contribution to Behçet’s disease. Methods Genotypes of all reported missense ERAP1 gene variants with 1000 Genomes EUR super-population frequency greater than 1% were determined in 1,900 Behçet’s disease cases and 1,779 controls from Turkey. ERAP1 protein allotypes and their contributions to Behçe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 17 publications
(14 reference statements)
2
59
1
Order By: Relevance
“…Our family study also showed haplotype frequencies very close to those predicted by imputation from the large AS association study using the Immunochip custom genotyping platform (1). They are also consistent with previous family studies on ERAP1/ERAP2 haplotypic associations with AS in Canada and recent results from a large study of ERAP1 haplotypes in Behçet's syndrome (14,15). Overall our results confirm that ERAP1 alleles with K528 predispose to AS and that 528R is protective.…”
Section: Discussionsupporting
confidence: 82%
“…Our family study also showed haplotype frequencies very close to those predicted by imputation from the large AS association study using the Immunochip custom genotyping platform (1). They are also consistent with previous family studies on ERAP1/ERAP2 haplotypic associations with AS in Canada and recent results from a large study of ERAP1 haplotypes in Behçet's syndrome (14,15). Overall our results confirm that ERAP1 alleles with K528 predispose to AS and that 528R is protective.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, Hap10 and Hap2 of ERAP1 play a central role for patients within the MHC-I-opathy cluster: patients with psoriasis have an increased risk of uveitis [31]. Patients with AS and BD often have uveitis [11,42], and the ERAP1 associations are much stronger in cases that developed uveitis compared with cases with systemic disease alone [2,32]. Although HLA-A29 is also common in some non-European populations, Hap10 and particularly the Hap10-ERAP2 (rs2287987-rs10044354) haplotype are less common in Asian and African individuals compared to European and, as we show, if present may exhibit different functional effects on ERAP1, which may explain why Birdshot primarily affects patients of European descent [18].…”
Section: Discussionmentioning
confidence: 99%
“…Hap10 plays a central role for patients within the MHC-I-opathy cluster: Hap10 is the major risk ERAP1 allotype for patients with Behçet's Disease (BD) and is highly protective against AS (i.e. Hap1/Hap2 are risk haplotypes for AS) [11,12]. Hap10 is associates with BD assuming a recessive model (Birdshot, p meta-recessive = 9.81 × 10 −5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in a recent study, an ERAP1 protein allotype called Hap10 was associated with BD risk in HLA-B*51 carriers following the recessive model [33]. This haplotype carried five non-ancestral alleles, including p.Asp575Asn and p.Arg725Gln, and it was found previously to have lower peptide-trimming activity [29,34].…”
Section: Pathogenesis Via Altered Peptide Presentationmentioning
confidence: 93%